ANALISIS PENERAPAN SISTEM PENGUPAHAN BAWON PADA MASA PANEN PADI DALAM PERSPEKTIF EKONOMI ISLAM - Erik; Eja Armaz Hardi; Fauzan Ramli (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2023)
The bawon wage system is a system using rice reaping wages, namely (profit sharing). the distribution of bawon is 20% profit sharing for Bawon workers and 80% for rice field owners, the wage system applied in bandar jaya village is 5:1. describes a problem by examining existing data in Bandar Jaya Village, Rantau Rasau District and then analyzing it based on the Islamic Economic Perspective. Using the data collection method, observation, interviews, and documentation were found. From the results of this study, it was found that: (1) in Bandar Jaya Village, the bawon system was considered a very suitable wage system compared to daily and piece rate wages. They considered the value of rice to be more valuable than rice. other than that money for rice that has good quality can be made as seeds. And for owning land the bawon system can reduce the risks that might occur, such as fraud and the quality of work and the bawon system also strengthens the brotherhood of mutual help between landowners and Bawon workers. (2) seen from the Perspective of Islamic Economics The "bawon" wage system that has been used by farmers in Bandar Jaya Village, Tanjung Jabung Timur District, is a rice farming wage system that begins with a work agreement, categorized as valid and justifiable, although there is an element of ambiguity in wages because it is not yet known the full yield of the crop. However, the previous rice field owner was able to estimate the yield he would get. With other considerations, the practice of the bawon/wages contract is valid according to Islamic law because it is in accordance with the rules,